STRATEGI PENINGKATAN MOTIVASI KERJA PEGAWAI PADA KANTOR PELAYANAN PAJAK PRATAMA PALEMBANG ILIR BARAT - Johanes Ardian; Hendra Risqo; Nurbaiti Nurbaiti; Yulia Afrina; Nurindani Nurindani (Jurnal Ilmu Administrasi dan Studi Kebijakan (JIASK), 2021)
The title of this research is "Strategy for Increasing Employee Work Motivation at the Pratama Palembang Ilir Barat Tax Service Office", aims 1) How is the strategy to increase employee work motivation at the Palembang Ilir Barat Pratama Tax Service Office 2) What factors support and hinder the increase in work motivation employee at the West Palembang Ilir Tax Service Office?The type of research used is descriptive qualitative method, that descriptive method is a method in examining the status of a group of people, an object, a set of conditions, a system of thought or a class of events in the present. The data analysis techniques used are: a) Data reduction; retrieve data for analysis purposes. b) Data Display; so that the data is easier to understand then the data is collected in the form of matrices, drawings or schematics so that the analysis carried out will be more accurate c) Conclusion and verification is the stage of drawing conclusions, after reducing and displaying the data. The results of the analysis are: 1). The strategy used to increase the motivation of employees of the Pratama Palembang Ilir Barat Tax Service Office by using the SO strategy is to use the power to take advantage of opportunities by utilizing trained employees with educational backgrounds in the field of taxation with government regulations that require certified implementing staff (staff). 2) Internal factors in the implementation of improving employee performance in the Primary Tax Office, namely a) strength consisting of (a). Number of human resources; (b). Better payroll/remuneration system; (3). Educational background, expertise and skills of reliable employees; (4). Implementation of In house Training for certain cases. b) weaknesses consisting of: (a). Lots of employees, but cramped office space; (b). Inadequate facilities and infrastructure; (c). Old computer, slow, not always updated; (d). The average boss is already dusk, less credible. And external factors, namely (a) opportunities consisting of . Opportunities in career development ; promotion etc; (b). Compete to get an S, A, B, C rating; (c). Opportunities to continue education (many scholarships etc.); (d). Opportunity to work as well as possible to return to homebase. b) threats consisting of: (a). Uncooperative taxpayers; (b). Less democratic leaders; (c). The work area is wide, making it difficult to supervise to achieve the acceptance target; (d). Often interacts with taxpayers so that bribery is possible.